How Do Situational Cues Influence Honest and Deceptive Impression Management in Selection Interviews? A Grounded Theory Study - Benedikt Bill; Annika Schmitz-Wilhelmy; Rebecca Heinzelmann; Klaus G. Melchers (Journal of Business and Psychology, 2024)
Abstract In selection interviews, most applicants use deceptive as well as honest impression management (IM) to seem like a better candidate. To date, however, little is known about situational cues that determine these behaviors, about the psychological processes in the form of affect and cognitions caused by situational cues, and about how these processes affect subsequent impression management. Given that the absence of a conceptual model that explicitly considers both kinds of IM is holding the literature back, we explored situational cues and associated psychological processes. To do so, we conducted a qualitative study using a Grounded Theory approach. Based on the data, we were able to establish a main model and three submodels that include both deceptive and honest impression management. The submodels describe situational cues related to either the interviewer or interview content. In these submodels, we were also able to identify several cues that have not yet received attention in the literature. We also found that these situational cues are associated with positive and/or negative affect, and that affect subsequently influences IM behavior. In addition, we were able to identify IM tactics that go beyond the existing literature.
Keywords: 330; Personnel selection; Faking; Impression management; Job interviews; Affect